Dark Triad Personality and Student Anti-Corruption Perceptions - Heryadi, Adi; Anditya, Ariesta Wibisono; Rahmawati, Diah Suci (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Several previous studies suggested that personality factors influence corrupt behavior (Abidin and Siswadi, 2015), Zhao et al. (2016). A survey by Matulessy et al. (2021) and research by Putri and Rahayu (2021) found that dark personality (Paulhus and Williams, 2002) is a factor that can influence corrupt behavior. The last two studies used civil servants and the private sector as research subjects. This research aims to determine the relationship between students' dark personality or dark triad personality and students' anti-corruption perceptions. This research involved 125 respondents who were students at the Unjaya Faculty of Economics and Social Sciences and were selected using a non-random sampling method. The data collection tool in this research was the Dark Triad Personality Scale. Adapted from the Jones and Paulhus Short Dark Triad (SD3) measurement instrument and has a coefficient valueCronbach alpha of .820, according to Hasanati & Istiqomah (2018), with a coefficient value Back alpha of .960. The findings show a relationship between dark triad personality and student anti-corruption attitudes. The correlation coefficient (correlation Pearson) is .220, and the significance level is .000. The correlation coefficient is more significant than .05 (p < .05), and the one-sided significance level is less than .05 (p < .05). Therefore, this relationship is considered vital.